Types and effectiveness of mental health promotion programmes for young people in sub-Saharan Africa: A systematic review - Tholene Sodi; Katlego Rantho; Frans Koketso Matlakala; Pamela Wadende; Deborah Ikhile; Samuel Oluwasogo Dada; Diana Frost; Paulette Henry; Utek Ishaku; Michael Obeng Brown; David Musoke; Shai Nkoana; et al. (Cambridge Prisms: Global Mental Health)
Studies show that mental health promotion is an effective strategy that can reduce the burden of mental health disorders and improve overall well-being in both children and adults. In addition to promoting high levels of mental well-being and preventing the onset of mental illness, these mental health promotion programmes, including mental illness prevention interventions, help increase levels of mental health literacy in community members. While there is evidence showing the effectiveness of mental health promotion, much of what is known about this field is informed by studies conducted in high-income countries. There is a need to gather evidence about the effectiveness of such interventions in low- and middle-income countries (LMICs) where mental health services are often inadequate. In this systematic review, we synthesised the available published primary evidence from sub-Saharan Africa (SSA) on the types and effectiveness of mental health promotion programmes for young people. We performed a search of selected global databases (PubMed, PsycINFO, ScienceDirect and Google Scholar) and regional databases (Sabinet African Journals). We included observational, mixed methods, trials, pilots and quantitative original papers published from 2013 to 2023. We used the Mixed Methods Appraisal Tool (MMAT) to evaluate the quality of methods in selected studies, and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement (PRISMA-2020) for reporting the evidence gathered. We identified 15 types of youth mental health promotion and illness prevention interventions. Among those identified, we found that school-based interventions enhanced mental health literacy, mental health-seeking behaviours and self-assurance and confidence among young people. Family-based interventions also showed a potential to improve relationships between young people and their caregivers. Future studies should explore how to further strengthen school- and family-based interventions that promote mental health among young people.